Inhibiting protein phosphatase 2A increases the antitumor effect of protein arginine methyltransferase 5 inhibition in models of glioblastoma. Issue 9 (8th February 2021) - Otani, Yoshihiro; Sur, Hannah P; Rachaiah, Guruprasad; Namagiri, Sriya; Chowdhury, Ashis; Lewis, Cole T; Shimizu, Toshihiko; Gangaplara, Arunakumar; Wang, Xiang; Vézina, Amélie; Maric, Dragan; Jackson, Sadhana; et al.
Abstract: Background: Despite multi-model therapy of maximal surgical resection, radiation, chemotherapy, and tumor-treating fields, the median survival of glioblastoma (GBM) patients is less than 15 months. Protein arginine methyltransferase 5 (PRMT5) catalyzes the symmetric dimethylation of arginine residues and is overexpressed in GBM. Inhibition of PRMT5 causes senescence in stem-like GBM tumor cells. LB100, a first-in-class small molecular inhibitor of protein phosphatase 2A (PP2A), can sensitize therapy-resistant tumor cells. Here, we tested the anti-GBM effect of concurrent PRMT5 and PP2A inhibition. Methods: Patient-derived primary GBM neurospheres (GBMNS), transfected with PRMT5 target-specific siRNA, were treated with LB100 and subjected to in vitro assays including PP2A activity and western blot. The intracranial mouse xenograft model was used to test the in vivo antitumor efficacy of combination treatment. Results: We found that PRMT5 depletion increased PP2A activity in GBMNS. LB100 treatment significantly reduced the viability of PRMT5-depleted GBMNS compared to PRMT5-intact GBMNS. LB100 enhanced G1 cell cycle arrest induced by PRMT5 depletion. Combination therapy also increased the expression of phospho-MLKL. Necrostatin-1 rescued PRMT5-depleted cells from the cytotoxic effects of LB100, indicating that necroptosis caused the enhanced cytotoxicity of combination therapy. In the in vivo mouse tumor xenograft model, LB100 treatment combined with transient depletion of PRMT5 significantly decreased tumor size and prolonged survival, while LB100 treatment alone had no survival benefit. Conclusion: Overall, combined PRMT5 and PP2A inhibition had significantly greater antitumor effects than PRMT5 inhibition alone.